Women in mid-life and older age in recovery from illicit drug use: connecting and belonging - Shaw, April (Frontiers in Psychiatry, 2023)
Background Establishing and maintaining healthy social connections and relationships are important in encouraging a sense of belonging that can help mid-life and older aged women in recovery from illicit drug use. This paper contributes to an under-researched area of substance use recovery among women in mid-life and older age by asking what influence social relationships have on their sense of self as they age into recovery from illicit drugs. Methods In-depth qualitative interviews were undertaken with 19 women in the United Kingdom who self-identified as ‘in recovery’ from illicit drug use. The interviews were transcribed verbatim and analyzed using Braun and Clarke’s thematic analysis techniques. The study received ethical approval from the University of Glasgow. Results As their drug use progressed, the women experienced feelings of estrangement and separation from others. Entering and maintaining a healthy recovery from drug use required the women to break their connections to people considered disruptive or challenging. Creating and setting boundaries enabled some of the women to gain a sense of control over their relationships and recovery. Positive reinforcement from others was pivotal to the process of the women’s self-acceptance, contributing to better self-concepts that helped them maintain their recovery. Discussion This investigation into substance use recovery among women in mid-life and older age offers new insights into the relationship challenges they face. It offers suggestions for further research that could support the development of family support programs for mid-life and older age women in active drug use or recovery.